2022
DOI: 10.3390/app12146932
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rotor-Stator Spacing on Compressor Performance at Variable Operating Conditions

Abstract: This paper investigates the effect of rotor-stator spacing and operating conditions on compressor performance and the rotor-stator interaction mechanism. We focus on the interaction between the rotor wake and the stator’s flow field through several unsteady numerical simulations aiming at a transonic compressor stage in the equal radius flow path with two-axial spacing at three operating conditions. The simulation results indicate that the time-averaged efficiency almost declined by 0.6 points due to mixing lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…To explore the mechanism producing SFAF, we use monitoring points on the stream surface at mid-span to obtain time-resolved data, as illustrated in Figure 19. The method to generate the monitor points is based on a parameterized blade profile, as proposed in our previous study [32]. The monitor points are set in the rotor, and the axial spacing from the rotor-stator spacing to the LE.…”
Section: Analysis Of the Baseline Stagementioning
confidence: 99%
“…To explore the mechanism producing SFAF, we use monitoring points on the stream surface at mid-span to obtain time-resolved data, as illustrated in Figure 19. The method to generate the monitor points is based on a parameterized blade profile, as proposed in our previous study [32]. The monitor points are set in the rotor, and the axial spacing from the rotor-stator spacing to the LE.…”
Section: Analysis Of the Baseline Stagementioning
confidence: 99%
“…Substantial studies [5][6][7][8] have shown that such a boundary setting fosters computational stability at lower flow conditions in compressors. Furthermore, Niu et al investigated the impact of rotor-stator spacing on compressor performance across various conditions, specifying the outlet boundary as the radial profile of averaged static pressure in accordance with stable findings [9]. Moreover, Wang et al [10] examined the pipelines of two-stage centrifugal compressors, obtaining the characteristic curves by outlining the exit flow rates.…”
Section: Introductionmentioning
confidence: 98%
“…Based on the acceptable boundary disturbance parameters, the influence of the total pressure and temperature on the aerodynamic response is discussed from the experimental and simulation perspectives. Niu [11] studied the influence of the operating conditions on the compressor's performance and the mechanism of dynamic and static interaction. Rzadkowski [12,13] numerically calculated the unsteady low-frequency aerodynamic forces of the blades caused by an asymmetric upstream flow.…”
Section: Introductionmentioning
confidence: 99%